Β/δ-PrIT1, a highly insecticidal toxin from the venom of the Brazilian spider Phoneutria reidyi (F.O. Pickard-Cambridge, 1897). (15th September 2015) - de Oliveira, Leida Calegário; Campos, Fabiana V.; Figueiredo, Suely Gomes; Cordeiro, Marta N.; Adaime, Beatriz R.; Richardson, Michael; Pimenta, Adriano M.C.; Martin-Eauclaire, Marie-France; Beirão, Paulo S.L.; De Lima, Maria Elena
Abstract: A potent insecticidal toxin, β/δ- PrIT1, molecular mass of 5598.86 [M + H] +, was characterized from Phoneutria reidyi spider venom. Its partial amino acid sequence showed high similarity with insecticidal spider toxins from the genus Phoneutria . β/δ-PrIT1 was very toxic (LD50 = 4 nmol/g) to flies ( Musca domestica ), but not to mice ( Mus musculus ). Kinetic studies showed that 125 I-β/δ-PrIT1 binds to two distinct sites in insect sodium channels, with close affinity (Kd1 = 34.7 pM and Kd2 = 35.1 pM). Its association is rather fast (t1/2(1) = 1.4 min, t1/2(2) = 8.5 min) and its dissociation is a slower process (t1/2(1) = 5.4 min, t1/2(2) = 32.8 min). On rat brain synaptosomes β/δ-PrIT1 partially competed (∼30%) with the beta-toxin 125 I-CssIV, but did not compete with the alpha-toxin of reference 125 I-AaII, nor with the beta-toxin 125 I-TsVII. On cockroach nerve cord synaptosomes, β/δ-PrIT1 did not compete with the anti-insect toxin 125 I-LqqIT1, but it competed (IC50 = 80 pM) with the "alpha-like" toxin 125 I-BomIV. In cockroach neurons, β/δ-PrIT1 inhibited the inactivation of Nav-channels and it shifted the sodium channel activation to hyperpolarizing potentials. These results indicate two different binding sites for β/δ-PrIT1, leading to two different pharmacological responses. β/δ-PrIT1 is one of the most toxic spider toxins to insects without apparent toxicity to mammals, and provide new model for the development of insecticides. Highlights: First highly toxic anti-insect toxin purified from the Brazilian spider P honeutria reidyi . Toxin affinity to insect synaptosomes in the pM range. Electrophysiological data show alpha and beta-type effects.